Changes in the Transcriptome and Proteome of Cartilage in Microtia. Issue 7 (October 2021) - Dong, Weiwei; Jiang, Haiyue; He, Leren; Pan, Bo; Yang, Qinghua
Abstract : Abstract: Congenital microtia is a severe physiological defect and is among the most common craniofacial defects. It is characterized by severe auricle dysplasia, external auditory canal atresia or stenosis, and middle ear malformation, though inner ear development is mostly normal with some hearing occurring through bone conduction. Auricular reconstruction is the only treatment for congenital microtia. In this study, the authors integrated messenger ribonucleic acid and mass spectrometry data of cartilage obtained from the affected and unaffected sides of 16 unilateral microtia patients who had undergone ear reconstruction surgery. The authors next performed functional analyses to investigate differences in the proteome of the affected and unaffected ears to elicit molecular pathways involved in microtia pathogenesis. The authors collected 16 pairs samples. Proteomic and transcriptomic analyses identified 47 genes that were differentially expressed in affected and unaffected cartilage. Integrated pathway analysis implicated the involvement of genes related to cell adhesion, extracellular matrix organization, and cell migration in disease progression. Through the integration of gene and protein expression data in human primary chondrocytes, the authors identified molecular markers of microtia progression that were replicated across independent datasets and that have translational potential.